Investigation and mitigation of a failure at the Taxiarches canal of Mornos aqueduct - Mourtzas, N. D.; Gkiolas, A.; Vakiris, D.; Soulis, V. (Bulletin of the Geological Society of Greece, 2013)
The sudden soil fracture and failure at the Taxiarches canal of Mornos Aqueduct of the Athens Water Supply and Sewerage Company (EYDAP SA), took place approximately 540m after the exit of Elikonas tunnel and resulted in failure and displacement of the canal segments along an 80m long section. Due to the failure the water supply was interrupted and two extensive gullies, spaced 75m apart, were created by the water outflow. The water discharge resulted in subsoil erosion and transportation of vast masses of geomaterial and two of the canal segments downhill. The debris flow destroyed part of Prodromos-Saranti Road, swapping along olive cultivations and causing extensive damage to Saranti settlement. The failure of the canal occurred in an area of steep morphology, at the front of an overthrust, within tectonic breccia and calcareous-clayey material of chaotic structure and reduced mechanical properties, vulnerable to erosion. The boundaries of the main fracture were defined by the thrust geometry. Τhe study of permanent remedial measures included excavation of a cut in the natural slope on the uphill side of the failure, construction of a bypass pipe founded on bedrock and of an anchored pile wall with pre-stressed anchors on the downhill side of the new pipe, excavation and removal of the temporary fill and finally construction of a reinforced fill for rehabilitation of the slide area.